2014
DOI: 10.1186/1753-6561-8-s1-s100
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree-based random effect tests to screen gene pathways

Abstract: The new generation of sequencing platforms opens new horizons in the genetics field. It is possible to exhaustively assay all genetic variants in an individual and search for phenotypic associations. The whole genome sequencing approach, when applied to a large human sample like the San Antonio Family Study, detects a very large number (>25 million) of single nucleotide variants along with other more complex variants. The analytical challenges imposed by this number of variants are formidable, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The first two principal components (PC1, PC2) (estimated as described in Peralta et al [7] and Almeida et al [8]), were added to account for any unknown population substructure that might be present.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first two principal components (PC1, PC2) (estimated as described in Peralta et al [7] and Almeida et al [8]), were added to account for any unknown population substructure that might be present.…”
Section: Methodsmentioning
confidence: 99%
“…We used the variance component model previously described in Peralta et al [7] and Almeida et al [8], in conjunction with the nonweighted and FP-weighted covariance kernels derived from the SNP dosages described above, to estimate the proportion of the phenotypic variance, h geff 2 , explained by allele-specific genetic variants found within DHSs in an unrelated CEU-CEPH individual. The h geff 2 variance component, and its significance, was estimated for each real and simulated expression phenotype using SOLAR, a flexible genetic variance component analysis program with a focus on general pedigrees [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea could be extended to computing heritabilities on a chromosomal or a gene segment basis (Yang et al, 2011a). One could also leverage this approach to compute the K relevant for a metabolic pathway and to estimate pathway-specific variance components (Almeida et al, 2012). We have shown that it is possible to accurately recover both total and local (i.e., QTL-specific) heritability estimates by using only empirical GRKs in a known pedigree situation (Day-Williams et al, 2011).…”
Section: Analysis Of Empirical Grksmentioning
confidence: 99%
“…Large genetic and epidemiologic projects are beginning to utilize whole genome sequencing (WGS) to identify genetic variants (especially novel rare variants) that could explain the missing heritability paradox [1]. The paradox had been formulated during the genome wide association (GWA) era; those platforms are based on the CDCV (common disease common variant) premise.…”
Section: Introductionmentioning
confidence: 99%